Enhancing the Accessibility of Knowledge Graph Question Answering Systems through Multilingualization - Perevalov, Aleksandr; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (16th IEEE International Conference on Semantic Computing, ICSC 2022, Laguna Hills, CA, USA, January 26-28, 2022)

Tab2Onto: Unsupervised Semantification with Knowledge Graph Embeddings - Zahera, Hamada M.; Heindorf, Stefan; Balke, Stefan; Haupt, Jonas; Voigt, Martin; Walter, Carolin; Witter, Fabian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2022 Satellite Events - Hersonissos, Crete, Greece, May 29 - June 2, 2022, Proceedings)

CausalQA: A Benchmark for Causal Question Answering - Bondarenko, Alexander; Wolska, Magdalena; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille; Stein, Benno; Braslavski, Pavel; Hagen, Matthias; Potthast, Martin (Proceedings of the 29th International Conference on Computational Linguistics, COLING 2022, Gyeongju, Republic of Korea, October 12-17, 2022)

Knowledge Graphs - Hogan, Aidan; Blomqvist, Eva; Cochez, Michael; d’Amato, Claudia; de Melo, Gerard; Gutierrez, Claudio; Kirrane, Sabrina; Gayo, José Emilio Labra; Navigli, Roberto; Neumaier, Sebastian; Ngonga Ngomo, Axel-Cyrille; Polleres, Axel; et al. (ACM Comput. Surv.)

A survey of RDF stores & SPARQL engines for querying knowledge graphs - Ali, Waqas; Saleem, Muhammad; Yao, Bin; Hogan, Aidan; Ngonga Ngomo, Axel-Cyrille (VLDB J.)

Hardware-agnostic computation for large-scale knowledge graph embeddings - Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Softw. Impacts)

Secure learning-based MPC via garbled circuit - Tjell, Katrine; Schluter, Nils; Binfet, Philipp; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Encrypted dynamic control with unlimited operating time via FIR filters - Schluter, Nils; Neuhaus, Matthias; Schulze Darup, Moritz (2021 European Control Conference (ECC))

Tailored neural networks for learning optimal value functions in MPC - Teichrib, Dieter; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Behavioral Economics for Human-in-the-Loop Control Systems Design: Overconfidence and the Hot Hand Fallacy - Protte, Marius; Fahr, Rene; Quevedo, Daniel E. (IEEE Control Systems)
Keywords: Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering; Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering

„LauRa - In der Lehramtsausbildung Reflexionskompetenz analysieren“. Untersuchungen zum Verhältnis von Theorie, Praxis und Reflexion im Rahmen der Professionalisierung angehender Lehrpersonen. - Meier, Jana
Der Förderung von Reflexionskompetenz wird für die Professionalisierung angehender Lehrkräfte eine hohe Bedeutung für die Relationierung zwischen Theorie und Praxis zugeschrieben. In dieser Arbeit wird den übergeordneten Fragestellungen nachgegangen, inwiefern es Lehramtsstudierenden durch Reflexionsgelegenheiten im Studium gelingt, ihr theoretisches Wissen mit praktischen Erfahrungen in Beziehung zu setzen und in welchem Zusammenhang die Reflexionskompetenz zu bestimmten Fördermaßnahmen (Portfolioarbeit) und Settings (Microteaching) sowie zu anderen Facetten professioneller Handlungskompetenz (Professionswissen, Einstellungen, Motivation) steht. Auf Basis einer kompetenztheoretischen Modellierung von Reflexion wurde hierzu die Reflexionsperformanz von Lehramtsstudierenden erfasst, um Rückschlüsse auf reflexionsbezogene Denkprozesse ziehen zu können. Die Auswertungen erfolgten qualitativ inhaltsanalytisch und wurden an teilweise quantifiziert, um statistische Analysen durchführen zu können. Insgesamt zeigen die Befunde der drei Teilstudien, dass die Reflexionsperformanz insbesondere dann von höherer Qualität ist, wenn theoretische Inhalte explizit mit praktischen Erfahrungen relationiert werden. Positive Einstellungen gegenüber Reflexion unterstützen die Reflexionsperformanz. Das bildungswissenschaftliche Professionswissen der Studierenden kann darüber hinaus Unterschiede in der Reflexionsperformanz erklären.

„Reflexion ist erzwungenes Nachdenken“ – Zusammenhänge zwischen dem Reflexionsverständnis Lehramtsstudierender & Facetten ihrer Reflexionskompetenz. - Meier, Jana; Vogelsang, Christoph; Watson, Christina; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

Der Zyklus von Planung und Reflexion – Zusammenhänge zwischen der generischen Unterrichtsplanungsfähigkeit und der Reflexionskompetenz angehender Lehrkräfte. - Meier, Jana; Küth, Simon; Scholl, Daniel; Vogelsang, Christoph; Watson, Christina

Erfassung der Reflexionskompetenz angehender Lehrpersonen mittels (offener) Situationsvignetten. - Meier, Jana; Vogelsang, Christoph

Rollenspiele als Übungs- & Prüfungsformate in der universitären Lehramtsausbildung. - Meier, Jana; Vogelsang, Christoph; Wotschel, Philipp; Janzen, Thomas

Einschätzungen Studierender zu Prüfungsformaten im Lehramtsstudium. - Vogelsang, Christoph; Meier, Jana; Wotschel, Philipp; Janzen, Thomas

Validierung von Testinstrumenten durch Testmotivationsindikatoren. - Watson, Christina; Meier, Jana; Küth, Simon; Scholl, Daniel; Seifert, Andreas; Vogelsang, Christoph

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Regularity of Lie groups - Hanusch, Maximilian (Communications in Analysis and Geometry)
Keywords: regularity of Lie groups

Analysis 1 und 2 Skript/Buch - Hanusch, Maximilian

Tackling the Accuracy–Interpretability Trade-off: Interpretable Deep Learning Models for Satellite Image-based Real Estate Appraisal - Kucklick, Jan-Peter; Müller, Oliver (ACM Transactions on Management Information Systems)
Deep learning models fuel many modern decision support systems, because they typically provide high predictive performance. Among other domains, deep learning is used in real-estate appraisal, where it allows to extend the analysis from hard facts only (e.g., size, age) to also consider more implicit information about the location or appearance of houses in the form of image data. However, one downside of deep learning models is their intransparent mechanic of decision making, which leads to a trade-off between accuracy and interpretability. This limits their applicability for tasks where a justification of the decision is necessary. Therefore, in this paper, we first combine different perspectives on interpretability into a multi-dimensional framework for a socio-technical perspective on explainable artificial intelligence. Second, we measure the performance gains of using multi-view deep learning which leverages additional image data (satellite images) for real estate appraisal. Third, we propose and test a novel post-hoc explainability method called Grad-Ram. This modified version of Grad-Cam mitigates the intransparency of convolutional neural networks (CNNs) for predicting continuous outcome variables. With this, we try to reduce the accuracy-interpretability trade-off of multi-view deep learning models. Our proposed network architecture outperforms traditional hedonic regression models by 34% in terms of MAE. Furthermore, we find that the used satellite images are the second most important predictor after square feet in our model and that the network learns interpretable patterns about the neighborhood structure and density.
Keywords: Interpretability; Convolutional Neural Network; Accuracy-Interpretability Trade-Of; Real Estate Appraisal; Hedonic Pricing; Grad-Ram

Correction: Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehmann, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Keywords: Orthopedics and Sports Medicine

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Hyphenation of ultra-high-performance liquid chromatography and ion mobility mass spectrometry for the analysis of sequence-defined oligomers with different functionalities and tacticity - Berg, Marie-Theres; Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
In recent years, sequence-defined oligomers (SDOs) gained increasing interest due to their perfectly controlled molecular structure, thus providing defined properties. In order to tune the properties, different functionalities need to be incorporated into the oligomers and the chain tacticity needs to be controlled. Beside the synthesis of SDOs, suitable methods need to be found to analyze the molecular structure. In this work, oligomers exhibiting an alternating or block-wise sequence of side chain functionalities were analyzed using a hyphenation of ultra-high-performance liquid chromatography and electrospray ionization mass spectrometry enhanced by ion mobility separation (IMS). Moieties in the side chains were varied according to polarity and bulkiness. Moreover, chain tacticity was varied. Drift times in the IMS cell and the corresponding collision cross section (CCS) values were shown to be individual parameters allowing the identification of SDOs, even in the case that SDO structures only differ in sequence or tacticity of side chain functionalities. Thus, a library of CCS values was obtained as reference used for the analysis of complex mixtures of SDOs.
Keywords: Ultra-high-performance liquid chromatography; ion mobility separation; mass spectrometry; LC-MS hyphenation; sequence-defined oligomers

Quinuclidine-Immobilized Porous Polymeric Microparticles as a Compelling Catalyst for the Baylis–Hillman Reaction - Kumar, Amit; Kuckling, Dirk; Nebhani, Leena (ACS Applied Polymer Materials)
Poly(quinuclidin-3-yl methacrylate-co-divinylbenzene) microparticles having porous as well as nonporous morphology and varying contents of quinuclidine functionality were synthesized by distillation–precipitation polymerization. Further, the synthesized microparticles were explored to catalyze the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Porous and nonporous microparticles functionalized with a catalytic moiety with a loading of 70% (labeled as P70 and NP70) were employed to optimize reaction parameters such as water content, solvent, and temperature for the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Using optimal conditions, the catalytic efficiency of porous and nonporous microparticles at different feed compositions was determined. Porous microparticles containing 70% of quinuclidine (P70) displayed 100% conversion within 16 h at 50 °C, while nonporous microparticles containing 70% of quinuclidine (NP70) displayed a relatively less catalytic conversion, which is attributed to their lower surface area. Furthermore, the catalytic activity of porous microparticles containing 70% of quinuclidine (P70) for the Baylis–Hillman reaction involving a variety of aryl aldehyde derivatives was determined, where the microparticles displayed impressive catalytic efficiency. In addition, the reusability of the microparticles functionalized with a catalytic moiety was evaluated for five cycles of catalytic reaction.
Keywords: distillation−precipitation polymerization; porous microparticles; heterogeneous catalysis Baylis−Hillman reaction; reusable catalyst

Branching analysis of β-cyclodextrin-based poly(N-isopropylacrylamide) star polymers using triple detection SEC - Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
For the first time, poly(N-isopropylacrylamide) (PNIPAAm) star polymers with a β-cyclodextrin core are characterized in detail by size-exclusion chromatography (SEC) with triple detection to experimentally verify the number of arms. A combination of a refractive index detector, multi-angle laser light scattering detector, and an online-viscosimeter was used for branching analysis. At first, the SEC system was calibrated and the detector setup was validated using linear polystyrene reference polymers. The applicability of the established triple detection SEC for branching analysis was shown by the analysis of two commercially available polystyrene star polymers. Due to the high molar masses of the star polymers, both the contraction ratio g and g′ could be determined independently, thus allowing the calculation of the viscosity shielding ratio ε. Finally, the branching analysis of the PNIPAAm star polymers could experimentally confirm the assumed arm number of up to 21 arms. Moreover, an increasingly compact molecular structure and the influence of the arm number on the viscosity shielding ratio could be shown.
Keywords: Size-exclusion chromatography; triple detection; branching analysis; star polymers; poly(N-isopropylacrylamide); β-cyclodextrin

Uniqueness of the Inverse First Passage Time Problem and the Shape of the Shiryaev boundary - Kolb, Martin; Klump, Alexander (Theory of Probability and its Applications)

Does education have an impact on patience and risk willingness? - Tawiah, Beatrice Baaba (Applied Economics)

On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Persistence of autoregressive sequences with logarithmic tails - Denisov, Denis; Hinrichs, Günter; Kolb, Martin; Wachtel, Vitali (Electronic Journal of Probability)
We consider autoregressive sequences Xn = aXn−1 + ξn and Mn = max{aMn−1 , ξn} with a constant a ∈ (0, 1) and with positive, in- dependent and identically distributed innovations {ξk }. It is known that if P(ξ1 > x) ∼ d log x with some d ∈ (0, − log a) then the chains Xn and Mn are null recurrent. We investigate the tail behaviour of recurrence times in this case of logarithmically decaying tails. More precisely, we show that the tails of recurrence times are regularly varying of index −1 − d/ log a. We also prove limit theorems for Xn and Mn conditioned to stay over a fixed level x0. Furthermore, we study tail asymptotics for recurrence times of Xn and Mn in the case when these chains are positive recurrent and the tail of log ξ1 is subexponential.

Green Deals Gain Steam - Kengelbach, Jens; Keienburg, Georg; Söllner, Tobias; Wang, Yiran; Sievers, Sönke; Friedmann, Daniel; Nielsen, Jesper (BCG M&A Report 2022)

Do Green Deals Create Value? - Kengelbach, Jens; Friedman, Daniel; Keienburg, Georg; Degen, Dominik; Söllner, Tobias; Wang, Yiran; Sievers, Sönke (BCG M&A Report 2022)

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Schärfung der Sinne. Josef Winklers Mikroästhetik im Kontext kleiner Prosaformen der Moderne - Öhlschläger, Claudia (Inter- und transmediale Ästhetik bei Josef Winkler)

Evaluating database systems relying on secure multiparty computation - Anonymous, A

Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Alfred Anderschs "Die Rote" mit Antonioni gelesen - Öhlschläger, Claudia (Das Italien des Alfred Andersch. Interkulturelle und intermediale Konstellationen)

Lattice Revocation Mechanisms - Lohse, Jan

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Exploring the effects of physics explainer videos and written explanations on declarative knowledge and the illusion of understanding - Kulgemeyer, Christoph; Hörnlein, Madeleine; Sterzing, Fabian (International Journal of Science Education)
Keywords: Education

Wie können Erklärvideos zum Erwerb physikalischen Konzeptwissens beitragen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

Democracy ≠ Democracy. Creating digital infographics to compare different democratic systems. - Janzen, Thomas (Englisch betrifft uns)

Geschlechtsidentität - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Sexuelle Orientierung - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)